A Structured Approach to Teaching and Learning Robotics - Meti, Vinod Kumar V.; Sadalagi, Pooja; Giriyapur, A. C.; Siddhalingeshwar, I. G. (Journal of Engineering Education Transformations, 2018)
Students are not passionate enough about conventional teaching techniques because too often, we hear from students that conventional teaching is boring and that they cannot relate to or understand the course that is presented to them each day in class. Rather than feel disheartened, we need to understand that we have before us both a challenge and an opportunity. Project-based learning (PBL) experiences will help us figure out how to make learning come alive for our engineering students. Project-based learning goes beyond generating student interest. Due to these reasons twenty-first century students are moving towards modern learning approaches rather than conventional learning. This paper presents the conceptual analysis of learning approaches involving use of simulation software, robots and solving real-time problems. Learning can be made more fun and interesting through practical application of concepts. Learning by actual implementation of theoretical concepts, provides students good hands-on and makes them ready for the industry.Result analysis show that performance of the students has improved and also quality of course projects is increased. Thus, we can conclude that students are attracted towards the course and also found to improve their learning skills in the context of course project work.